Pengaruh Pemberian Ekstrak Buah Kelor (Moringa oleifera) Terhadap Penurunan Kadar Kolestrol Pada Darah Hewan Mencit (Mus musculus) - Zulviana, Eva; Rahman, Nurdin; Supriadi, Supriadi (Universitas Tadulako, 2017)
This study aimed to identify bioactive compounds of moringa (moringa oleifera) extracts and determine the effective concentration on lowering blood cholesterol levels of mice. The animals used were 15 male mice induced by propylthiouracil and fat food diet. The mice were divided randomly into 5 groups with different treatment groups. The first, the second, and the third treatments were given moringa extracts each with a concentration of 10, 20% and 40%. The fourth treatment group was given food fat diet and propiltiorasil as a positive control, and the fifth treatment was given standard food and distilled water as a negative control. Data were analyzed using a statistical analysis of variance (ANOVA) test followed by Duncan test. The results showed that moringa fruit extract contains alkaloids, saponins, flavonoids, and tannins. Moringa fruit extract can lower blood cholesterol levels of mice with the most effective concentration of 10%.